Impacts of climate change and sea-level rise on the coastal geological environment of Quang Nam province, Vietnam - Nguyen Yen T. N.; Doan Phuong T. K.; Vo Duong N.; Nguyen Quan T.; Nguyen Phong C. (Open Geosciences)
The increasing frequency and severity of climate change and rising sea levels pose significant challenges worldwide, including in Vietnam. Quang Nam province’s coastal region features an extensive distribution of Quaternary deposits, dating from the Early Pleistocene to the Late Holocene. These unconsolidated sediments, along with widespread undivided Quaternary formations, contribute to the area’s geological characteristics. The province’s low-lying terrain, shallow groundwater reserves, and extensive 125 km-long coastline heighten its susceptibility to environmental changes. In this study, the MIKE SHE, MIKE 21 FM, and MIKE FLOOD models were applied for calibration (1980–2000) and validation (2001–2016). Simulations were conducted using rainfall and sea-level rise data under the representative concentration pathway (RCP) 4.5 and RCP 8.5 scenarios. The results show significant issues, including saltwater intrusion, rising groundwater levels, and flooding. Under a scenario involving a level-13+ storm and flood discharge with a 10% frequency, the flooded area is estimated at 538.3 km2. In a scenario with reservoirs tested for flood discharge, the flooded area increases to 721.9 km2. When reservoirs discharge floods with a frequency of P = 10%, the affected area is 504.1 km2, while reservoir flood discharge following design standards results in a flooded area of 530.1 km2. Riverbank and coastal erosion have caused adverse effects on groundwater resources. The extent of saltwater intrusion has been increasing over time. Under the RCP 4.5 scenario, the area affected by land subsidence due to saltwater intrusion is projected to expand from 88.02 km2 in 2020 to 90.82 km2 in 2030 and 93.89 km2 in 2050.